(untitled) (Global Journal of Science Frontier Research, 2019)
This study aims to describe and classify the kuweni mango plants in Bungku Tengah Subdistrict especially in Matansala and Bahoruru Villages through morphological characters and leaf anatomy to look for parent trees. Observations of morphological characteristics were carried out in the villages of Matansala and Bahoruru, while leaf anatomical observations were carried out in the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Tadulako University, from December 2016 to May 2017. Observation were carried out under a microscope with a scale of 400 times magnification. After all the primary data was collected, a dendrogram analysis was performed using the SYSTAT 8.0 program. The results showed morphological and anatomical characters observed based on cluster analysis described in the form of dendrograms. Unselected accessions in the combined dendrogram are caused by the concept of distance used. In the dendrogram analysis of the distance cluster formed, it can be interpreted that the farther the distance to the right, the more various similarities of characters from the accession. Conversely, the farther the distance to the left, the more similar the character of the kuweni accession.